2017
DOI: 10.1186/s12991-017-0163-1
|View full text |Cite
|
Sign up to set email alerts
|

Mental, neurologic, and substance use (MNS) disorders among street homeless people in Ethiopia

Abstract: BackgroundAbout 25–60% of the homeless population is reported to have some form of mental disorder. To our knowledge, there are no studies aimed at the screening, diagnosis, treatment, care, rehabilitation, and support of homeless people with mental, neurologic, and substance use (MNS) disorders in general in Ethiopia. This is the first study of its kind in Africa which was aimed at screening, diagnosis, care, treatment, rehabilitation, and support of homeless individuals with possible MNS disorder.MethodsComm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 48 publications
0
48
0
5
Order By: Relevance
“…The records were mostly published in the last decade (2009-2019). Apart from one study from North Africa [40], all other studies were conducted in sub- Sahara Africa predominantly South Africa [30,[36][37][38]44] and Ethiopia [11,39,42,45,46]. The remaining studies were conducted in Nigeria [35], Ghana [41], and Mozambique [43].…”
Section: Selection Of Sources Of Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…The records were mostly published in the last decade (2009-2019). Apart from one study from North Africa [40], all other studies were conducted in sub- Sahara Africa predominantly South Africa [30,[36][37][38]44] and Ethiopia [11,39,42,45,46]. The remaining studies were conducted in Nigeria [35], Ghana [41], and Mozambique [43].…”
Section: Selection Of Sources Of Evidencementioning
confidence: 99%
“…One study sampled from both streets and shelters [38], and one study failed to mention category of homeless people studied [40]. Only two study assessed the duration of homelessness and found that most participants were chronically homeless [11,39]. Two studies sampled only women [37,45] and the remainder recruited both males and females.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations